SPE EUROPEC/EAGE Annual Conference and Exhibition 2011
DOI: 10.2118/142896-ms
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Reservoir Simulation Workflow for Unconventional Resource Play: Bakken Case Study

Abstract: It is widely accepted that unconventional resources hold enormous reserve potential. However, complex fluid flow physics and completion/stimulation practices pose a unique challenge in estimating reserves or making long-term production forecast for these unconventional reservoirs, as traditional methods are most often not applicable. This paper proposes the application of a probabilistic reservoir simulation workflow to provide realistic range of production forecasts with successful application in the Bakken u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Yu and Sepehrnoori [40] have optimized the well spacing and pointed out that four horizontal wells are often drilled in the area of 1 mile × 2 miles. Luo et al [41] found that the number of perforation stages is averagely 30 for each long lateral. Hence, we set a simulation model in the field scale, with the dimension of 10,560 ft, 5280 ft, and 40 ft in x, y, and z direction, respectively.…”
Section: Flow Governing Equationsmentioning
confidence: 99%
“…Yu and Sepehrnoori [40] have optimized the well spacing and pointed out that four horizontal wells are often drilled in the area of 1 mile × 2 miles. Luo et al [41] found that the number of perforation stages is averagely 30 for each long lateral. Hence, we set a simulation model in the field scale, with the dimension of 10,560 ft, 5280 ft, and 40 ft in x, y, and z direction, respectively.…”
Section: Flow Governing Equationsmentioning
confidence: 99%
“…The downhole pressure data is used to optimize artificial lift, maximize well productivity, and identify potential and developing production problems (Luo et al 2011). In special cases, such as liquids-rich unconventional gas reservoirs, real-time downhole pressure and temperature data is used to maintain production conditions in the near-wellbore/fracture region above the dewpoint of gas to avoid condensate drop out in the reservoir that could impair inflow performance (Altman et al 2014).…”
Section: Unconventional Reservoirs: Unique Requirementsmentioning
confidence: 99%